Method for producing porous cellulose beads

JP7629692B2Active Publication Date: 2025-02-14KANEKA CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020064177
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-31
Publication Date
2025-02-14
Estimated Expiration
2040-03-31

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、毒性·腐食性の高い副原料を使わず、工業的に不利である煩雑な工程を経ることなく簡便に、抗体吸着に適したセルロースビーズを製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629692000001
    Figure 0007629692000001
  • Figure 0007629692000002
    Figure 0007629692000002
  • Figure 0007629692000003
    Figure 0007629692000003
Patent Text Reader

Abstract

To provide a method for easily producing cellulose beads suitable for antibody adsorption without using an auxiliary raw material having high toxicity and corrosiveness and without going through a complicated process which is industrially disadvantageous.SOLUTION: There is provided a method for producing porous cross-linked cellulose beads including the steps of: (a) dissolving cellulose in a mixed solution of sodium hydroxide, lithium hydroxide, urea and water at a temperature of 5°C or lower and -20°C or higher to prepare a cellulose solution; (b) heating the cellulose solution to 10°C or higher and 40°C or lower; (c) dispersing the cellulose solution into a dispersion medium of 10°C or higher and 40°C or lower to prepare an emulsion; (d) bringing the emulsion into contact with a coagulation solvent to precipitate cellulose beads; and (e) cross-linking the precipitated cellulose beads, wherein a molar ratio of sodium hydroxide / lithium hydroxide in the step (a) is 0.3 / 0.7 to 0.8 / 0.2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing porous cellulose beads. [Background technology]

[0002] Porous cellulose beads have the advantage of being safer and less prone to non-specific adsorption than other synthetic polymers, and are used as substrates for various adsorbents, such as adsorbents for various types of chromatography and affinity adsorbents. In particular, affinity adsorbents can efficiently purify target substances and reduce the concentration of unnecessary substances, and therefore have been used as medical adsorbents and adsorbents for purifying antibody drugs. In particular, adsorbents in which protein A is immobilized on a porous carrier as an affinity ligand have attracted attention as adsorbents for treating rheumatism, hemophilia, and dilated cardiomyopathy or as medical adsorbents (e.g., Non-Patent Document 1, Non-Patent Document 2).

[0003] The production of porous cellulose beads involves many complicated steps compared to ordinary synthetic polymers, since it has been believed that dissolving cellulose is difficult. One of these methods involves dissolving and solidifying cellulose in a highly corrosive and toxic solvent, such as an aqueous solution of calcium thiocyanate, which makes it difficult to set up equipment (e.g., Patent Document 1). It is known that the cellulose solution used in this method exhibits peculiar behavior, and that the porous cellulose beads obtained by this method have fairly large pores and a wide pore size distribution (e.g., Non-Patent Document 3). Therefore, when the porous cellulose beads obtained by this method are used as an adsorbent for antibodies, etc., it is not expected to show high adsorption performance because of the small specific surface area. On the other hand, a method is exemplified in which a substituent is added to the hydroxyl group of cellulose in order to increase the solubility of cellulose, the cellulose is dissolved in a general-purpose solvent, granulated, and the substituent is removed after granulation to obtain a porous cellulose-based carrier (e.g., Patent Document 2). However, the process is complicated, and the molecular weight decreases during the process of adding and removing the substituent, and it tends to be difficult to obtain mechanical strength suitable for use in high-speed processing and large-scale use, which are required in recent years.

[0004] On the other hand, a method of dissolving cellulose in a low-temperature mixed solution of alkali / urea / water has been reported (Non-Patent Document 4). This dissolution method has a low environmental impact and the dissolution process is not complicated, so various studies have been conducted on it. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2009-242770 [Patent Document 2] International Publication WO2006 / 025371 [Non-patent literature]

[0006] [Non-Patent Document 1] Annals of the New York Academy of Sciences,Vol.1051,(2005),p.635-646 [Non-Patent Document 2] American Heart Journal,Vol.152,Number 4,(2006),p.712e1-712e6 [Non-Patent Document 3] Macromolecular Bioscience, vol.5, (2005), p.539-548 [Non-Patent Document 4] Journal of Chromatography,Vol.316,(1984),p.311-332 Summary of the Invention [Problem to be solved by the invention]

[0007] The objective of the present invention is to develop cellulose beads with a pore structure suitable for antibody adsorption, which can be produced simply and efficiently, without using highly toxic or corrosive secondary materials, and without going through complicated processes that are industrially disadvantageous. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above problems, the inventors discovered that cellulose beads having an optimal structure for antibody adsorption can be produced by using a mixed solution of sodium hydroxide, lithium hydroxide, urea and water, thereby completing the present invention.

[0009] Therefore, one aspect of the present invention relates to a method for producing porous crosslinked cellulose beads, the method comprising the steps of: (a) dissolving cellulose in a mixed solution of sodium hydroxide, lithium hydroxide, urea and water at -5°C or lower and -20°C or higher to prepare a cellulose solution; (b) heating the cellulose solution to 10°C or higher and 40°C or lower; (c) dispersing the cellulose solution in a dispersion medium at 10°C or higher and 40°C or lower to prepare an emulsion; (d) contacting the emulsion with a coagulation solvent to precipitate cellulose beads; and (e) crosslinking the precipitated cellulose beads, the method being characterized in that the molar ratio of sodium hydroxide / lithium hydroxide in the step (a) is 0.3 / 0.7 to 0.8 / 0.2. Effect of the Invention

[0010] According to the present invention, cellulose beads suitable for antibody adsorption can be produced simply and easily without using highly toxic or corrosive secondary materials or going through complicated processes that are industrially disadvantageous. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] An embodiment of the present invention will be described in detail below. In this specification, unless otherwise specified, "A to B" representing a numerical range means "A or more, B or less." In addition, all documents described in this specification are incorporated herein by reference.

[0012] 1. Overview of the Invention The method for producing porous cellulose beads according to one embodiment of the present invention (hereinafter referred to as "this production method") includes the steps of (a) dissolving cellulose in a mixed solution of sodium hydroxide, lithium hydroxide, urea and water at -5°C or lower and -20°C or higher to prepare a cellulose solution, (b) heating the cellulose solution to 10°C or higher and 40°C or lower, (c) dispersing the cellulose solution in a dispersion medium at 10°C or higher and 40°C or lower to prepare an emulsion, (d) contacting the emulsion with a coagulation solvent to precipitate cellulose beads, and (e) crosslinking the precipitated cellulose beads. The present applicant has already developed the fact that porous cellulose can be obtained by dispersing cellulose in a low-temperature aqueous sodium hydroxide solution and contacting it with a coagulation solvent (International Publication WO2012 / 121258, etc.).

[0013] Although the reason is unclear, the inventors surprisingly discovered for the first time that crosslinked cellulose beads with pores suitable for antibody adsorption can be produced by using multiple alkaline substances in combination rather than a single type of alkaline substance.

[0014] The configuration of this manufacturing method will be described in detail below.

[0015] 2. Method for producing porous cellulose beads The present production method includes the following steps (a) and (b) as essential steps. Step (a): dissolving cellulose in a mixed solution of sodium hydroxide, lithium hydroxide, urea and water at a temperature of -5°C or lower and -20°C or higher to prepare a cellulose solution. Step (b): heating the cellulose solution prepared in step (a) to a temperature of 10° C. or higher and 40° C. or lower. Step (c): A step of dispersing the cellulose solution prepared in step (b) in a dispersion medium having a temperature of 10° C. or higher and 40° C. or lower to prepare an emulsion. Step (d): A step of contacting the emulsion prepared in step (c) with a coagulation solvent to precipitate cellulose beads. Step (e): Crosslinking the cellulose beads precipitated in step (d). Each step of the method of the present invention will be described below.

[0016] (Step (a)) In step (a) of this production method, cellulose is dissolved in a mixed solution of sodium hydroxide, lithium hydroxide, urea and water at −5° C. or lower and −20° C. or higher to prepare a cellulose solution.

[0017] Here, the molar ratio of sodium hydroxide / lithium hydroxide is preferably 0.3 / 0.7 to 0.8 / 0.2, more preferably 0.4 / 0.6 to 0.7 / 0.3, and even more preferably 0.45 / 0.55 to 0.65 / 0.35. If the molar ratio of sodium hydroxide is too high, the pore radius becomes too large for antibody adsorption, and if the molar ratio of sodium hydroxide is too low, the pore radius becomes too small for antibody adsorption.

[0018] In one embodiment of the present invention, the total concentration of sodium hydroxide and lithium hydroxide in the mixed solution of sodium hydroxide, lithium hydroxide, urea and water is preferably 5% by weight to 20% by weight, more preferably 6% by weight to 15% by weight, and even more preferably 7% by weight to 12% by weight. If the concentration is within the above range, cellulose can be dissolved well.

[0019] In one embodiment of the present invention, the urea concentration in the mixed solution of sodium hydroxide, lithium hydroxide, urea and water is preferably 10% by weight to 20% by weight, more preferably 11% by weight to 18% by weight, and even more preferably 11% by weight to 16% by weight. If the concentration is within the above range, cellulose can be dissolved well.

[0020] In one embodiment of the present invention, the cellulose concentration of the cellulose solution is preferably 3% by weight or more and 9% by weight or less. If the concentration is within the above range, the cellulose can be dissolved satisfactorily.

[0021] In one embodiment of the present invention, the molecular weight of the cellulose raw material used is not particularly limited, but the degree of polymerization is preferably 100 to 1000. It is further preferably 150 to 900, and even more preferably 200 to 800. When the cellulose molecular weight is within the above range, the cellulose is easily dissolved.

[0022] In one embodiment of the present invention, the temperature of the cellulose solution is preferably −5° C. to −20° C., more preferably −8° C. to −19° C., and even more preferably −10° C. to −17° C. If the temperature is −5° C. or higher, cellulose is difficult to dissolve, and if the temperature is −20° C. or lower, the cellulose solution freezes, resulting in poor operability.

[0023] (Step (b)) In step (b) of the present production method, the cellulose solution prepared in step (a) is heated to 10° C. to 40° C., more preferably 15° C. to 30° C., and even more preferably 20° C. to 28° C. If the heating temperature is within the above range, cellulose does not precipitate and the solution viscosity does not increase, allowing for a suitable operation.

[0024] (Process (c)) In step (c) of this production method, the cellulose solution prepared in step (b) is dispersed in a dispersion medium to prepare an emulsion.

[0025] In one embodiment of the present invention, the dispersion medium is not particularly limited as long as it is not miscible with the cellulose solution, and examples thereof include hydrocarbon solvents, animal and vegetable oils and fats, hydrogenated animal and vegetable oils and fats, fatty acid glycerides, aliphatic hydrocarbon solvents, and aromatic hydrocarbon solvents. In addition, a surfactant such as a nonionic surfactant may be added to the dispersion medium.

[0026] Examples of the hydrocarbon solvent include hexane, decane, and liquid paraffin. Examples of the animal and vegetable oils include palm oil, shea fat, monkey fat, illipe fat, lard, beef tallow, rapeseed oil, rice oil, peanut oil, olive oil, corn oil, soybean oil, perilla oil, cottonseed oil, sunflower oil, evening primrose oil, sesame oil, safflower oil, coconut oil, cacao butter, palm kernel oil, fish oil, wakame seaweed oil, and kelp oil. Examples of the hydrogenated animal and vegetable oils include palm hardened oil, palm extremely hardened oil, rapeseed hardened oil, rapeseed extremely hardened oil, soybean hardened oil, lard hardened oil, and fish oil hardened oil. Examples of the fatty acid glyceride include tri-, di-, and mono-glycerides, and examples of the fatty acid glyceride include stearic glyceride, palmitic glyceride, and lauric glyceride. Examples of the aliphatic hydrocarbon solvent include beeswax, candelilla wax, rice bran wax, etc. Examples of the aromatic hydrocarbon solvent include benzene, toluene, chlorobenzene, dichlorobenzene, etc.

[0027] To prepare an emulsion, a suitable amount of a surfactant may be added to the dispersion medium. Examples of the surfactant include sorbitan fatty acid esters such as sorbitan laurate, sorbitan stearate, sorbitan oleate, and sorbitan trioleate, and polyglycerin fatty acid esters such as polyglycerin polyricinoleate, decaglycerin oleate, and decaglycerin stearate.

[0028] In one embodiment of the present invention, the amount of the dispersion medium used is not particularly limited, but may be an amount that can sufficiently disperse the cellulose solution prepared in step (b). For example, the amount may be 1 to 10 times the volume of the cellulose solution. More preferably, the amount is 2 to 8 times, and more preferably, 4 to 10 times. If the amount of the dispersion medium used is outside the above range, there is a risk of excessive increase in the amount of waste liquid.

[0029] The emulsion may be prepared by a conventional method, for example, by vigorously stirring a mixture containing the cellulose solution, a dispersion medium, and a surfactant.

[0030] (Step (d)) In step (d) of this production method, the emulsion prepared in step (c) is brought into contact with a coagulation solvent to produce porous cellulose beads.

[0031] The solidification solvent is not particularly limited as long as it has affinity for the cellulose solution, but examples thereof include alcohol-based solvents and mixed solvents of water and alcohol-based solvents. Examples of alcohol-based solvents include C ethanol, n-propanol, isopropanol, n-butanol, isobutanol, s-butanol, and t-butanol. 1-4 The ratio of water to the alcohol-based solvent in the mixed solvent of water and the alcohol-based solvent can be, for example, water:alcohol-based solvent=80:20 to 1:99 by volume.

[0032] In one embodiment of the present invention, the coagulation method is not particularly limited, but since the emulsion may be unstable, it is preferable to add the coagulation solvent while vigorously stirring the emulsion to prevent the droplets from bonding together.

[0033] After the addition of the coagulation solvent, the coagulated porous cellulose beads may be separated by filtration, centrifugation, etc., and washed with water, alcohol, etc. The obtained porous cellulose beads may be classified using a sieve or the like to make the particle size uniform.

[0034] (Step (e)) In step (e) of this production method, the cellulose beads produced in step (d) are crosslinked with a crosslinking agent to produce porous crosslinked cellulose beads.

[0035] The crosslinking agent has two or more reactive groups capable of forming covalent bonds with hydroxyl groups on cellulose and can crosslink between cellulose molecules. There are no particular limitations on the crosslinking conditions or crosslinking agents for the crosslinked porous cellulose particles that can be used in the present invention. For example, the method described in WO2008 / 146906 can be used. The entire contents of this international publication are incorporated herein by reference.

[0036] Examples of the crosslinking agent include halohydrins such as epichlorohydrin, epibromohydrin, and dichlorohydrin; bifunctional bisepoxides (bisoxiranes); and polyfunctional polyepoxides (polyoxiranes). The crosslinking agents may be used alone or in combination of two or more.

[0037] The solvent for the reaction of crosslinking the porous cellulose beads with a crosslinking agent may be appropriately selected, and examples of the solvent include water, as well as water-miscible organic solvents such as alcoholic solvents such as methanol, ethanol, isopropanol, and nitrile solvents such as acetonitrile. Two or more crosslinking reaction solvents may be mixed for use.

[0038] The crosslinking reaction may be carried out multiple times, and the reaction solvent or crosslinking agent may be changed each time. For example, the first crosslinking reaction may be carried out in a water-miscible organic solvent, and the final crosslinking reaction may be carried out in water. In this case, the solvent composition in the middle may be the same as or different from either the first or the final crosslinking reaction, or may be an intermediate composition between them. Furthermore, all the crosslinking reactions may be carried out in an aqueous solvent. The same applies to the crosslinking agent. When the crosslinking reaction is repeated multiple times, it is preferable to remove the crosslinking agent by washing the crosslinked porous cellulose beads with water or the like between each crosslinking reaction.

[0039] In order to promote the crosslinking reaction, a base may be added to the reaction solution. Examples of such bases include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal hydrogen carbonates such as sodium hydrogen carbonate and potassium hydrogen carbonate, alkali metal carbonates such as sodium carbonate and potassium carbonate, and organic bases such as triethylamine and pyridine.

[0040] After the crosslinking reaction, the porous crosslinked cellulose beads are insoluble and can be washed with a solvent such as water.

[0041] According to the present production method, crosslinked porous cellulose beads having excellent antibody adsorption properties can be obtained with high productivity.

[0042] [3. Porous cross-linked cellulose beads] The porous crosslinked cellulose beads according to one embodiment of the present invention (hereinafter referred to as "the present beads") have an intraparticle porosity of 90% or more, a pore radius of 35 to 50 nm, and a volume median diameter of 45 to 70 μm.

[0043] The present beads have the advantage of having excellent antibody adsorption capacity because they are produced by the present production method.

[0044] The volume median diameter of the present beads is not particularly limited, but from the viewpoint of achieving excellent dynamic antibody adsorption capacity, it is preferably 45 to 70 μm, more preferably 50 to 65 μm, and even more preferably 55 to 63 μm. The volume median diameter of the present beads is measured by the method described in the Examples.

[0045] From the viewpoint of achieving excellent dynamic antibody adsorption capacity, the intraparticle porosity of the present beads is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. The intraparticle porosity of the present beads is measured by the method described in the Examples.

[0046] From the viewpoint of achieving excellent dynamic antibody adsorption capacity, the pore radius of the present beads is preferably 35 to 50 nm, more preferably 37 to 48 nm, and even more preferably 40 to 45 nm. The average pore radius of the present beads is measured by the method described in the Examples.

[0047] The beads can be bound to a protein A ligand in order to specifically adsorb an antibody, and there are no particular limitations on the binding conditions or the protein A ligand. For example, the method described in WO2012 / 133349 can be used. The entire contents of this international publication are incorporated herein by reference.

[0048] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.

[0049] That is, one embodiment of the present invention is as follows. <1> (a) preparing a cellulose solution by dissolving cellulose in a mixed solution of sodium hydroxide, lithium hydroxide, urea and water at a temperature of -5°C or lower and -20°C or higher; (b) heating the cellulose solution to a temperature of 10° C. or higher and 40° C. or lower; (c) dispersing the cellulose solution in a dispersion medium having a temperature of 10° C. or higher and 40° C. or lower to prepare an emulsion; (d) contacting the emulsion with a coagulation solvent to precipitate cellulose beads; (e) a process for producing porous crosslinked cellulose beads, comprising the step of crosslinking the precipitated cellulose beads, A method for producing porous crosslinked cellulose beads, wherein the molar ratio of sodium hydroxide / lithium hydroxide in the step (a) is 0.3 / 0.7 to 0.8 / 0.2. <2> A method for producing porous crosslinked cellulose beads, wherein the mixed solution of sodium hydroxide, lithium hydroxide, urea and water in the step (a) has a urea concentration of 10% by weight to 20% by weight. <3> A method for producing porous crosslinked cellulose beads, characterized in that the cellulose solution has a cellulose concentration of 3% by weight or more and 9% by weight or less. <4> 1. A method for producing porous crosslinked cellulose beads, wherein the coagulation solvent is an alcohol-based solvent or a mixed solvent of water and an alcohol-based solvent. <5> Porous crosslinked cellulose beads having an intraparticle porosity of 90% or more, a pore radius of 35 nm to 50 nm, and a volume median diameter of 45 μm to 70 μm. EXAMPLES

[0050] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0051] [Measurement and evaluation methods] Measurements and evaluations in the Examples, Comparative Examples, and Production Examples were carried out by the following methods.

[0052] (Volume Median Diameter) The volume median diameter of the beads was measured using a HORIBA LA-950 laser diffraction / scattering particle size distribution analyzer.

[0053] (pore radius) 22.8 mL of the beads were dispersed in distilled water and degassed for 30 minutes. The degassed porous cellulose beads were packed into a column (GE Healthcare Japan "Tricorn 10 / 300"). Measurements were performed using a Shimadzu size exclusion chromatography system (including "DGU-20A3", "RID-10A", "LC-20AD", "SIL-20AC", and "CTO-20AC" and using "LCSolution" software).

[0054] As a marker, dextran or glucose shown in Table 1 was dissolved in 20 mM phosphate buffer (pH 7.5) containing 0.2 M NaCl and used.

[0055] [Table 1]

[0056] While passing 20 mM phosphate buffer (pH 7.5) containing 0.2 M NaCl through the column at a flow rate of 0.33 mL / min, the volume of the column other than the beads was measured. 7 A solution of dextran with a molecular weight of 4×10 was injected, and the amount of solution passed from the injection until a peak was observed on the RI monitor was measured. 7The concentration of the dextran solution was 10 mg / mL, and the injection volume was 40 μL. Next, the flow rate of each marker solution was calculated in the same manner. The measured values ​​were substituted into the following formula, K D The value was calculated. K D =(V R -V 0 ) / (V t -V 0 ) [In the formula, V R indicates the volume of each marker solution (mL) passed from the injection until a peak was observed, and V 0 is the molecular weight 4×10 7 V indicates the amount of dextran solution (mL) passed from the injection of the dextran solution until a peak is observed. t V indicates the volume of the bead pores in the column (mL). t is measured using a molecular weight 180 marker.] The intraparticle porosity is (V t -V 0 ) / V 0 It is expressed as:

[0057] K D The pore radius was calculated from the value of 0.01 and 0.02 by the following formula described in Non-Patent Document 4.

[0058]

number

[0059] r p is the average pore radius, s p indicates standard deviation.

[0060] (Measurement of dynamic adsorption amount) (1) Solution preparation The following solutions A to E and a neutralization solution were prepared and degassed before use. Solution A: A PBS buffer solution at pH 7.4 was prepared using Sigma's "Phosphate buffered saline" and distilled water. Solution B: A 35 mM sodium acetate solution at pH 3.5 was prepared using acetic acid, sodium acetate, and distilled water. Solution C: A 1M aqueous solution of acetic acid was prepared using acetic acid and distilled water. Solution D: A polyclonal antibody (Gammaguard, Baxter) and solution A were used to prepare an aqueous IgG solution with a concentration of 3 mg / mL. Solution E: An aqueous solution of sodium hydroxide and sodium chloride manufactured by Wako Pure Chemical Industries, Ltd., with concentrations of 0.1 N sodium hydroxide and 1 M sodium chloride, respectively, was prepared and used as an alkaline cleaning solution. Neutralizing solution: A 2M aqueous solution of tris(hydroxymethyl)aminomethane was prepared using tris(hydroxymethyl)aminomethane and ultrapure water.

[0061] (2) Filling and preparation AKTA Pure 150 (GE Healthcare) was used as the column chromatography apparatus, and 3 mL of the adsorbent sample was placed in a column with an inner diameter of 0.5 cm, with the adsorbent layer height set to 15 cm. A 0.2 M NaCl aqueous solution prepared from sodium chloride and distilled water was passed through the column at a flow rate of 3 mL / min for 10 minutes to fill the column with the adsorbent. A 15 mL collection tube was set in the fraction collector, and the collection tube for the eluate was previously filled with neutralizing solution.

[0062] (3) IgG purification 15 mL of solution A was passed through the column, followed by the required amount of solution D. Next, 12 mL of solution A was passed through, followed by 12 mL of solution B to elute IgG. Next, 9 mL of solution C, 15 mL of solution A, 9 mL of solution E, and 15 mL of solution A were passed through. The flow rates were 1 mL / min except for solution D, and the flow rate of solution D was adjusted to a predetermined retention time (RT). For example, the flow rate at RT 4 minutes was adjusted to 0.75 mL / min.

[0063] (4) Dynamic adsorption amount The dynamic adsorption amount of IgG was calculated from the amount of IgG adsorbed to the adsorbent until 5% of the IgG broke through and the volume of the adsorbent. This dynamic adsorption amount is called 5% DBC.

[0064] Example 1 (Preparation of cellulose solution) 30.2g of 48.0wt% sodium hydroxide (manufactured by Nacalai Tesque, Inc.) aqueous solution, 15.4g of lithium hydroxide monohydrate (manufactured by Kishida Chemical Co., Ltd.), 57.5g of urea (manufactured by Wako Pure Chemical Industries, Ltd.), and 200g of pure water were mixed and dissolved, and kept at 10°C to prepare an alkaline aqueous solution. 17g of powdered cellulose (manufactured by Nippon Paper Industries, W200G) was dispersed in 80g of water and added to the alkaline aqueous solution, and then the temperature was lowered to -12°C to dissolve the cellulose. The sodium hydroxide concentration of the solvent excluding the cellulose weight was 3.8% by weight, the lithium hydroxide concentration was 2.3% by weight, and the urea concentration was 15% by weight, and the sodium hydroxide molar amount / lithium hydroxide molar amount was 0.5 / 0.5. The cellulose solution was kept at -12°C for 60 minutes, and then heated to 40°C and kept for 30 minutes.

[0065] (Preparation of porous cellulose beads) 234.5g of Hicol K-230 (liquid paraffin, manufactured by Kaneda Co., Ltd.), 404.5g of Hicol K-290 (liquid paraffin, manufactured by Kaneda Co., Ltd.), and 9.8g of PR-100 (manufactured by Riken Vitamin Co., Ltd.) were placed in a cylindrical container with an inner diameter of 85 mm, stirred at 300 rpm, heated to 40°C, and 161g of the above cellulose solution was added and stirred to produce an emulsion. A three-stage stirring blade was used for stirring, with an inclined paddle, a flat turbine, and a disk turbine from the top. After stirring for 20 minutes, 150 ml of a coagulation solvent with a methanol / pure water volume ratio of 70 / 30 was added to obtain cellulose beads. The obtained cellulose beads were washed with isopropanol and then with water.

[0066] (Classification of cellulose beads) The remaining cellulose beads obtained were sieved using meshes with 38 μm and 90 μm openings to collect beads in the range of 38 μm to 90 μm.

[0067] (Cross-linking of cellulose beads) After replacing 100 mL of the liquid contained in the porous cellulose beads after classification with ethanol, the beads were transferred to a reaction vessel, and the total amount of cellulose particles and ethanol was adjusted to 125 g, and 80 mL of epichlorohydrin was added thereto. The solution temperature was adjusted to 40°C, and 96 mL of 1.8 N NaOH aqueous solution (prepared with sodium hydroxide and distilled water manufactured by Nacalai Tesque) was added to start the crosslinking reaction. 1.5 hours after the start of the reaction, 9.6 mL of 17.0 N NaOH aqueous solution was added, and 3 hours and 4.5 hours after the start of the reaction, 9.6 mL of 17.0 N NaOH aqueous solution was also added. 6 hours after the start of the reaction, the gel was collected and washed with distilled water with a volume 20 times or more that of the beads.

[0068] The crosslinked cellulose beads obtained by the above crosslinking reaction were transferred to a reaction vessel so that the total amount of cellulose beads and distilled water was 116.7 g. 37.8 g of sodium sulfate was added thereto and dissolved, after which 33 mL of epichlorohydrin was added and the mixture was kept at 40°C. 21 mL of 17.0 N NaOH aqueous solution was added to start the crosslinking reaction, and 5 mL of 17.0 N NaOH aqueous solution was added 2.5 hours after the start of the reaction. Five hours after the start of the reaction, the particles were collected and washed with distilled water with a volume 20 times or more that of the particles.

[0069] (Classification of porous cross-linked cellulose beads) The remaining cellulose beads were sieved using 38 μm and 75 μm meshes to collect beads in the range of 38 μm to 75 μm in size. The crosslinked cellulose beads had a volume median diameter of 61 μm, an average pore radius of 45.0 nm, and an intraparticle porosity of 98%.

[0070] Example 2 Crosslinked cellulose beads were obtained in the same manner as in Example 1, except that the heating temperature during preparation of the cellulose solution and the temperature during preparation of the porous cellulose beads were both 25° C. The resulting crosslinked cellulose beads had a volume median diameter of 60 μm, an average pore radius of 38.4 nm, and an intraparticle porosity of 97%.

[0071] Example 3 Crosslinked cellulose beads were obtained in the same manner as in Example 1, except that the urea concentration during preparation of the cellulose solution was 11.5% by weight. The resulting crosslinked cellulose beads had a volume median diameter of 60 μm, an average pore radius of 41.9 nm, and an intraparticle porosity of 98%.

[0072] Example 4 45.3g of 48.0wt% sodium hydroxide aqueous solution, 7.7g of lithium hydroxide monohydrate, 57.5g of urea, and 200g of pure water were mixed and dissolved, and kept at 10°C to prepare an alkaline aqueous solution. 17g of powdered cellulose was dispersed in 80g of water, added to the alkaline aqueous solution, and then the temperature was lowered to -12°C to dissolve the cellulose. The sodium hydroxide concentration of the solvent excluding the cellulose weight was 5.6% by weight, the lithium hydroxide concentration was 1.1% by weight, the urea concentration was 15% by weight, and the sodium hydroxide molar amount / lithium hydroxide molar amount was 0.25 / 0.75. The cellulose solution was kept at -12°C for 60 minutes, and then heated to 40°C and kept for 30 minutes. Crosslinked cellulose beads were obtained in the same manner as in Example 1. The volume median diameter of the obtained crosslinked cellulose beads was 60μm, the average pore radius was 39.9nm, and the intraparticle porosity was 98%.

[0073] Example 5 Crosslinked cellulose beads were obtained in the same manner as in Example 4, except that 150 ml of a coagulation solvent with a methanol / pure water volume ratio of 45 / 55 was added when preparing the porous cellulose beads. The resulting crosslinked cellulose beads had a volume median diameter of 62 μm, an average pore radius of 40.7 nm, and an intraparticle porosity of 94%.

[0074] Example 6 Except for changing the amount of cellulose to 14 g when preparing the porous cellulose beads, crosslinked cellulose beads were obtained in the same manner as in Example 1. The resulting crosslinked cellulose beads had a volume median diameter of 58 μm, an average pore radius of 44.9 nm, and an intraparticle porosity of 97%.

[0075] Comparative Example 1 52.5g of 48.0wt% sodium hydroxide aqueous solution and 46.0g of urea were mixed and dissolved and kept at 10°C to prepare an alkaline aqueous solution. 17g of powdered cellulose was dispersed in 283.5g of water and added to the alkaline aqueous solution, and then the temperature was lowered to -12°C to dissolve the cellulose. The sodium hydroxide concentration of the solvent excluding the cellulose weight was 6.7% by weight and the urea concentration was 12% by weight. The cellulose solution was kept at -12°C for 60 minutes, and then heated to 40°C and kept for 30 minutes. Except for this, crosslinked cellulose beads were obtained in the same manner as in Example 1. The volume median diameter of the obtained crosslinked cellulose beads was 60μm, the average pore radius was 51.2nm, and the intraparticle porosity was 90%.

[0076] Comparative Example 2 31.0g of lithium hydroxide monohydrate, 57.5g of urea, and 210g of pure water were mixed and dissolved, and kept at 10°C to prepare an alkaline aqueous solution. 17g of powdered cellulose was dispersed in 80g of water, added to the alkaline aqueous solution, and then the temperature was lowered to -12°C to dissolve the cellulose. The lithium hydroxide concentration of the solvent excluding the cellulose weight was 4.7% by weight, and the urea concentration was 15.2% by weight. Otherwise, crosslinked cellulose beads were obtained in the same manner as in Example 2. The volume median diameter of the obtained crosslinked cellulose beads was 58 μm, the average pore radius was 28.0 nm, and the intraparticle porosity was 95%.

[0077] Comparative Example 3 31.5g of lithium hydroxide monohydrate, 46.0g of urea, and 137.3g of pure water were mixed and dissolved, and kept at 10°C to prepare an alkaline aqueous solution. 17g of powdered cellulose was dispersed in 170g of water, added to the alkaline aqueous solution, and then the temperature was lowered to -12°C to dissolve the cellulose. The lithium hydroxide concentration of the solvent excluding the cellulose weight was 4.7% by weight, and the urea concentration was 12.0% by weight. The cellulose solution was kept at -12°C for 60 minutes, and then heated to 40°C and kept for 30 minutes. Except for this, crosslinked cellulose beads were obtained in the same manner as in Example 1. The volume median diameter of the obtained crosslinked cellulose beads was 60 μm, the average pore radius was 33.8 nm, and the intraparticle porosity was 98%.

[0078] [Test Example] The porous cross-linked cellulose beads obtained in Examples 1 to 5 and Comparative Examples 1 and 2 were bound to a protein A ligand by the following method.

[0079] (Epoxy ring-opening treatment) The resulting crosslinked beads and 50% slurry of water was heated in an autoclave at 121°C for 60 minutes to open the epoxy groups and convert them into diol groups. The disappearance of the epoxy groups can be confirmed using a phenolphthalein indicator.

[0080] (Aldehyde formation reaction) A buffer of pH 3.4 was prepared by adding water to 0.165 g of citric acid monohydrate and 0.0646 g of trisodium citrate dihydrate to make 100 mL.

[0081] The liquid portion was replaced with the above buffer using 3 times the amount of the above buffer for 3.5 mL of crosslinked cellulose beads, and the above buffer was further added to make the total amount 6.0 mL. 2.01 mL of 11.2 mg / mL sodium periodate aqueous solution was added and stirred at 25 ° C for 35 minutes. Then, it was filtered with a # 3 glass filter and washed with distilled water until the electrical conductivity of the filtrate was 1 μS / cm or less, and beads containing aldehyde groups were obtained. The electrical conductivity of the washed filtrate was measured with a conductivity meter ("ECTester10 Pure +" manufactured by EUTECH INSTRUMENTS). Under these reaction conditions, about 30 μmol of aldehyde groups were introduced per 1 mL of crosslinked porous cellulose beads.

[0082] (Protein A immobilization reaction) <Preparation of orientation-controlled alkaline-resistant protein A> With reference to WO2012 / 133349, a modified C domain 5-linked product described in WO2012 / 133349 was prepared as an orientation-controlled alkali-resistant protein A. The orientation-controlled alkali-resistant protein A has the amino acid sequence shown in SEQ ID NO: 2. The entire contents of WO2012 / 133349 are incorporated herein by reference. Hereinafter, "protein A" is abbreviated as "PA."

[0083] <Imination reaction - PA amount 20mg / mL> Water was added to 2.941 g of trisodium citrate dihydrate to make 100 mL, and a buffer of pH 8 was prepared. The above buffer was passed through the aldehyde group-containing beads in an amount three times the total amount (3.5 mL) on a glass filter #3, and the liquid portion in the beads was replaced with the above buffer. The aldehyde group-containing beads after replacement were placed in a reaction vessel, and PA immobilization buffer was added so that the total volume became 7.5 mL. Protein A was added in an amount of 20 mg (net amount) per 1 mL of beads. After adjusting the temperature to 6°C, the pH was adjusted to 12 using 0.08 N aqueous sodium hydroxide solution, and then stirred at 6°C overnight.

[0084] <Neutralization and reduction reaction> The imino reaction solution after overnight reaction was filtered, and the filtrate was measured by UV to determine the amount of PA immobilized. A 0.1M aqueous citric acid solution was added to the pH 8.0 Na citrate buffer to prepare a buffer adjusted to pH 5.0, and the liquid portion in the beads was replaced using the buffer in an amount three times that of the filtration beads. The total volume was adjusted to 7.0 mL with a pH 5.0 buffer and transferred to a reactor, and the mixture was stirred at 6°C for 4 hours while maintaining neutrality.

[0085] Thereafter, 1.93 mL of a 5.5% aqueous dimethylamine borane solution was added, and the reaction temperature was then raised to 25° C. and stirred overnight at 25° C. After the reaction, the beads were washed on a #3 glass filter with water in an amount three times the volume of the beads.

[0086] <Cleaning> On the #3 glass filter, 3 mL of 0.1 M citric acid (hereinafter referred to as "acid buffer") was passed per 1 mL of PA-immobilized beads to replace the liquid in the beads with the acid buffer. After the replacement, the PA-immobilized beads were transferred to a container, and the acid buffer was added to make the total volume 2 mL or more, and the mixture was stirred at 25°C for 30 minutes to perform acid washing.

[0087] Next, alkaline washing was carried out in the same manner, except that an aqueous solution of 0.05N sodium hydroxide and 1M sodium sulfate was used instead of the acid buffer.

[0088] Next, neutral washing was carried out in the same manner, except that a solution prepared by mixing 0.1 M citric acid and 0.1 M sodium citrate and adjusting the pH to 5.9 was used instead of the acid buffer.

[0089] After neutral washing, the beads were washed with distilled water until the electrical conductivity of the washing filtrate was 10 μs / cm or less, to obtain an adsorbent on which Protein A was immobilized.

[0090] The 5% DBC of the resulting adsorbent at RT4 is shown in Table 2.

[0091] [Table 2]

[0092] 〔result〕 Table 2 shows that the Examples have higher antibody adsorption performance than the Comparative Examples, and also shows that the pore radius is suitable for antibody adsorption only when the molar amount of sodium hydroxide / molar amount of lithium hydroxide in the cellulose solution is in a specific range.

[0093] From the above, it was found that the present production method makes it possible to produce porous cross-linked cellulose beads with high antibody adsorption capacity.

Claims

1. (a) preparing a cellulose solution by dissolving cellulose in a mixed solution of sodium hydroxide, lithium hydroxide, urea and water at a temperature of −5° C. or lower and −20° C. or higher; (b) heating the cellulose solution to 10° C. or higher and 40° C. or lower; (c) dispersing the cellulose solution in a dispersion medium having a temperature of 10° C. or higher and 40° C. or lower to prepare an emulsion; (d) contacting the emulsion with a coagulation solvent to precipitate cellulose beads; (e) a process for producing porous crosslinked cellulose beads, comprising the step of crosslinking the precipitated cellulose beads, A method for producing porous crosslinked cellulose beads, characterized in that the molar ratio of sodium hydroxide / lithium hydroxide in the step (a) is 0.3 / 0.7 to 0.8 / 0.

2.

2. 2. The method for producing porous crosslinked cellulose beads according to claim 1, wherein the urea concentration in the mixed solution of sodium hydroxide, lithium hydroxide, urea and water in step (a) is 10% by weight to 20% by weight.

3. 3. The method for producing porous crosslinked cellulose beads according to claim 1, wherein the cellulose concentration of the cellulose solution is 3% by weight or more and 9% by weight or less.

4. 4. The method for producing porous crosslinked cellulose beads according to claim 1, wherein the coagulation solvent is an alcohol-based solvent or a mixed solvent of water and an alcohol-based solvent.

Citation Information

Patent Citations

  • Porous cellulose microsphere adsorbent used for blood perfusion and preparation method thereof

    CN102794161A

  • Porous cellulose gel, method for producing the same and use thereof

    JP2009242770A

  • Method for manufacturing porous cellulose particle

    JP2016153449A

  • Granulocyte adsorbent

    WO2006025371A1

  • A method for preparing a cellulose based material

    WO2015142159A1